The Effect of Technology Readiness in IT Adoption on Organizational Context Among SMEs in the Suburbs of the Capital - Asrul, Sani; T.K.A, Rahman; Nur, Nawaningtyas; Agus, Budiyantara; Ninuk, Wiliani (2021)
The role of Information Technology (IT) in the digital era today is critical in the business environment. IT will provide convenience in the process of managing a Small and Medium Enterprises (SMEs) so that companies have a competitive advantage in the current economic development. Some research has been discussed the issue of IT adoption's impacts and uses in SMEs, in particular in the suburbs bordering the national capital. The purpose of this study is to identify the impact of IT and the factors that influence technology readiness in IT adoption the organizational context among SMEs located in the suburbs of Jakarta. This article follows a quantitative research approach based on case studies and structured questionnaires. The results of SEM analysis using the SmartPLS3 application give the results that awareness of technology, local government support, SME management support, and financial support are essential factors in IT adoption in SMEs. This article tries to look at other phenomena regarding the limitations SMEs have in using IT and tries to make a recommendation on how to overcome them. It is hoped that this research will contribute to the development of information systems models both in terms of academics and practitioner.